ANALYSIS OF FLAVONOID AND WATER-SOLUBLE VITAMIN CONTENT IN LOCAL WINES (Scientific journal of the Fergana State University, 2026)
In this study, the content of flavonoids and water-soluble vitamins in samples of white wine (Bayan shirey) and red wine (Hingdohni), produced from locally grown grape varieties, was analyzed using high-performance liquid chromatography. Although the total amount of flavonoids in white and red wines was found to be nearly the same, their distribution differed: hypolaetin was predominant in white wine, while rutin was dominant in red wine. Flavonoid glycosides accounted for 82.5% in red wine and 33.92% in white wine. The strong antioxidant gallic acid was detected in higher amounts in white wine. Analysis of water-soluble vitamins revealed the presence of vitamins B2, B3, B6, B9, and C in both wines, with the overall vitamin content slightly higher in white wine. These findings confirm the high biological value, antioxidant activity, and functional beverage potential of both white and red wines.